Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.7 - Factoring by Special Products - Exercise Set: 3

Answer

$(2x-3)^2$

Work Step by Step

The two numbers whose product is $ac= 4(9)=36 $ and whose sum is $b= -12 $ are $\{ -6,-6 \}$. Using these two numbers to decompose the middle term, then the factored form of the expression, $ 4x^2-12x+9 $, is \begin{array}{l}\require{cancel} 4x^2-6x-6x+9 \\\\= (4x^2-6x)-(6x-9) \\\\= 2x(2x-3)-3(2x-3) \\\\= (2x-3)(2x-3) \\\\= (2x-3)^2 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.